Awareness about breastfeeding benefits among mothers in maternity and children hospital of Buraidah Qassim region, Saudi Arabia - Alsoqeer, Asim A.; Alahmad, Ahmad M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Breastfeeding is a healthy, safe and economical way of providing proper and wholistic nutrition to the newborn. It reduces incidences of infection in the respiratory, gastrointestinal systems and systemic infections. As will as it deepens the bond between the mother and her child, and also it offers a number of health benefits to the mother. Despite these profound advantages, it remains under-fulfilled and sometimes missed altogether. The aim of the study is to assess the knowledge about breastfeeding benefits among mothers. Methods: The study involved 397 mothers visiting general pediatrics clinics at Maternity and Children Hospital of Buraidah, Qassim Region, Saudi Arabia from 18 March 2018 to 18 April 2018. Results: Most of the surveyed women were Saudi (93.5%), (46.1%) university or higher education level. (12.3%) rely on breastfeeding as the only source. (23.9%) were breastfeeding for more than 6 months. Some questions had as high correct answers as (49.2%), while others had as low correct answers as (20.4%), university or higher education level have the highest correct answers (73%). (61%) discussed the benefits of breastfeeding with a doctor and the correct answers were (72%) while (39%) didn't discuss and the correct answers were (65%). Conclusions: Analysis of the collected material on the surveyed women showed that Saudi women have insufficient knowledge about breastfeeding. Knowledge is improving after discussing with a doctor about breastfeeding benefits. Based on these results we highly recommend increasing the efforts to promote and endorse the benefits of breastfeeding by pediatricians and other health professionals.